A gamified web based system for computer programming learning - Polito, Giuseppina; Temperini, Marco (Computers and education. Artificial intelligence, 2021)
The availability of Automated Assessment tools for computer programming tasks can be a significant asset in Computer Science education. Systems providing such kind of service are built around an interface, allowing to administer the tasks (exercises to train programming skills), and show the results, accompanied by meaningful feedback. To produce such results, they apply techniques ranging from static analysis of program correctness, to testing-based evaluation. These systems can also support Competitive Programming, which is known to have educational meaning too. We developed the 2TSW system, supporting the automated correction of computer programming tasks, in a gamified web-based environment. The system let the student access a list of assignments (programming tasks), submit solutions to them, and have such solutions tested and graded. Accomplished tasks let the student gain experience points, represented also by medals, recognition of mastery on a topic, and improvements on a personal characterization of the student's status. The personal profile allows the student to monitor her/his proceedings and achievements. The gamified structure of the system, together with the availability of real-time automated assessment, offers the opportunity for an increasing level of students' personal engagement and motivation. Here we describe the system, and report on an experimentation, where students of a Bachelor Programme in Computer Engineering, first year, used 2TSW. In particular, we 1) present findings about the students' feedback, coming from a questionnaire administered after the experience, and 2) provide the reader with an analysis of the participation data, based on simple statistic tests. The students' feedback let us conclude that they appreciated the 2TSW gamified experience, perceived the system as useful, and maintained a high level of engagement. The data analysis allowed for less decisive conclusions, although it showed proof of the effectiveness of the system as a learning aid.